FIRST RECORD OF DOLICHOBOSTRYCHUS ANGUSTUS (STEINHEIL, 1872) (COLEOPTERA: BOSTRICHIDAE) FOR PERU - Juárez N., Gino (2015)
A new report for the country is cited: Dolichobostrychus angustus Steinheil (Bostrichidae) registered on the campus of the University of Piura, important area of equatorial dry forest of the Piura Region.